Spermatogenic and Androgenic Effect of The Root of Boscia Senegalensis (Per) Plant - Osuala, P. N; Okolo, R. U.; Etuk, E. U.; Bello, S. O.; Egua, M. O (British Journal of Healthcare and Medical Research, 2023)
More than 90% of male infertility is due to low sperm count, poor sperm quality or both. Boscia senegalensis locally known as Anza in Sokoto State, north-western Nigeria is used traditionally in treating fertility related problems. The plant root was washed and air dried pulverized into a dry powder and extracted with methanol. Eighty matured male rats were divided into four groups (A-D) of 20 rats each. Rats in group A, B and C were administered orally with 100mg/kg, 200mg/kg and 300mg/kg body weight respectively of the extract daily until the end of the experiment. Rats in group D served as a control and were given distilled water. Five rats from each group were anaesthetized with chloroform and sacrificed on day 0, 10, 20 and 30 of treatment. And for each batch the Sperm Concentration and Testosterone were determined. The data were analysed using a one way analysis of variance (ANOVA). The extract exhibited an inhibitory effect on the testosterone concentration at the 10th and 20th day of treatment at all dose levels. However, after the 30th day of treatment, the serum testosterone concentration (P<0.001) and epididymal sperm count (P<0.01) increased significantly at the 300mg/kg body weight dose. In conclusion, the extract of Boscia senegalensis may possess a significant androgenic and spermatogenic effect on a prolonged oral administration in a white albino rat which suggests that it may be useful in the management of male infertility problems.